AN EDUCATIONAL PROGRAM ACCORDING TO VISUAL THINKING NETWORKS FOR FLEXIBLE THINKING AND SOME BASIC FOOTBALL - Jabbar, Haidar Aayed (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2024)
The significance of this research stems from the implementation of an educational program designed around visual thinking networks, aimed at assessing its impact on flexible thinking and certain fundamental football skills among firstgrade students at Al Isra Boys Middle School, located in the Diwaniya district and governed by the Diwaniya Directorate of Education, during the 2022-2023 academic year. The total student body consists of 134 individuals, distributed across four classes. To align with the field application, the researcher employed an experimental design involving two equivalents' groups. A sample of 32 students was randomly selected from classes C and D, with class D serving as the experimental group and class C as the control group. The research involved utilizing the required tools and materials to implement the study steps, which included creating an educational program based on visual thinking networks, conducting a preliminary experiment, and carrying out the main field experiment. This process involved pre-tests, applying to the educational program, and conducting post-tests. The findings indicate that students benefit from an educational program centered on visual thinking networks to enhance their flexible thinking and fundamental football skills. The researcher recommends incorporating modern educational programs in lectures due to their crucial role in developing flexible thinking and improving basic football skills.